Pentafsiran Teks Hadith Berdasarkan Maqāṣid al-Sharī‘ah di Sisi Muḥaddithīn: Interpretation of Hadith Texts Based on Maqāṣid al-Sharī‘ah by Muḥaddithīn - Abd. Azid, Muhammad Adam; Ahmad, Khadher` (Online Journal of Research in Islamic Studies, 2019)
To interact with hadith Prophet SAW requires specific methods. This is to ensure hadith Prophet SAW can be understood precisely and meet the needs of Sharī‘ah. Interpreting hadith based on maqāṣid al-sharī‘ah is one of the methods proposed by the Islamic scholars in understanding the hadith. This research method is important to assure hadith is in line with the objectives of Syarak. This study aims to dissect the hadith text application based on maqāṣid al-sharī‘ah that is practiced by muḥaddithīn. This research is using qualitative research methods based on library research. The study found that maqāṣid al-sharī‘ah is certainly considered and be applied by muḥaddithīn in interpreting the hadith texts of Prophet SAW such as al-Khaṭṭābī, Ibn al-‘Arabī, al-Dihlawī and al-Qurṭubī.